The Relation of Cognitive Style (Divergent - Convergent Thinking) on Some Compound Fundamental Skills in First Class Soccer Clubs - Hassan, Mustafa Hussein; Hussein, Israa Jameel (Journal of Physical Education, 2021)
The researcher aimed at constructing cognitive style (divergent - convergent) for first-class soccer clubs as well as identifying the relationship between these cognitive styles and some fundamental compound soccer skills. The problem of the research lies in the lack of scale for measuring cognitive style (divergent – convergent) for soccer players as well as the absence of previous studies that tackled this style of thinking directly and its relationship with fundamental soccer skills. The researchers used the descriptive method on (150) soccer players from all clubs distributed as follows; (12) pilot study subjects, (78) construction subjects, and (60) application subjects. The questionnaire included (30) items. The data was collected and treated to conclude that there is a significant correlation between convergent thinking and compound fundamental skills.